Quantitative analysis of cefazolin sodium in lyophilized powder by infrared spectrophotometry: Green, low cost, fast and effective - Rechelo, Bárbara Saú [UNESP]; Kogawa, Ana Carolina [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Elsevier, 2019)
Cefazolin sodium is a broad-spectrum antibiotic used in the treatment of infectious diseases in humans and in the surgical prophylaxis. Thus, since a considerable number of people have access to this drug, it is of great interest of quality control. The aim of this study was development and validation of a green method by Fourier-Transform Infrared (FT-IR) transmission spectrophotometry for the quantification of cefazolin sodium in lyophilized powder. This technique is widely used in the pharmaceutical industry due to its ease of execution, low cost, safety and high precision and accuracy. It has been employed in the quality control routine of numerous pharmaceuticals in order to identify them and quantify their active principles. The proposed method was completely validated according ICH guidelines, showing selectivity, accuracy, precision, robustness and linearity. It was linear over the concentration range of 0.4–1.7 mg with correlation coefficient 0.999, limits of detection and quantification of 0.017 mg and 0.052 mg, respectively, precise, accurate and robust when changes in the time, pressure and mark of potassium bromide were carried out during the preparation of the pellets. The proposed method was successfully applied to the qualitative and quantitative quality control of cefazolin sodium in lyophilized powder. In addition, the method is considered green, clean and sustainable since it uses only a single reagent; it is a fast, low-cost and environmentally friendly method.
Keywords: Cefazolin sodium; Environmentally friendly method; Infrared spectrophotometry; Lyophilized powder